2015
DOI: 10.1038/srep08826
|View full text |Cite
|
Sign up to set email alerts
|

Renal progenitors derived from human iPSCs engraft and restore function in a mouse model of acute kidney injury

Abstract: Acute kidney injury (AKI) is one of the most relevant health issues, leading to millions of deaths. The magnitude of the phenomenon remarks the urgent need for innovative and effective therapeutic approaches. Cell-based therapy with renal progenitor cells (RPCs) has been proposed as a possible strategy. Studies have shown the feasibility of directing embryonic stem cells or induced Pluripotent Stem Cells (iPSCs) towards nephrogenic intermediate mesoderm and metanephric mesenchyme (MM). However, the functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 30 publications
(33 reference statements)
3
75
0
1
Order By: Relevance
“…Although several studies have reported renal progenitor induction from hESCs/iPSCs [14,32,[42][43][44], few + cells were analyzed by flow cytometry on culture day 28. The treatments at stages 1, 2, and 3 were the same as those used in A.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several studies have reported renal progenitor induction from hESCs/iPSCs [14,32,[42][43][44], few + cells were analyzed by flow cytometry on culture day 28. The treatments at stages 1, 2, and 3 were the same as those used in A.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, human fetal nephron progenitor cells have been shown to participate in the repair of renal tissue in experimental animal models of renal failure [13], suggesting that nephron progenitors generated from hiPSCs could be used for the development of regenerative medicine against renal diseases. However, few studies have demonstrated to date the therapeutic effects of hiPSCderived renal lineage cells against kidney disease [14].…”
Section: Introductionmentioning
confidence: 99%
“…Imberti et al have also reported that the transplantation of renal progenitors differentiated from human iPSCs improves AKI [42]. The group differentiated renal progenitors using numerous growth factors and compounds, including activin A, fibroblast growth factor (FGF)2, BMP7, glial cell line-derived neurotrophic factor (GDNF), retinoic acid, phosphoinositide 3-kinase (PI3K) inhibitor, and ras homologue gene family member A (RhoA) inhibitor.…”
Section: Renal Stem/progenitor Cells Differentiated From Pluripotent mentioning
confidence: 99%
“…Recently, two reports including one from our group have shown the therapeutic effects of renal progenitor cells differentiated from human iPSCs against AKI [41,42]. Because of the potential to infinitely proliferate and bypass immunorejection issues, iPSCs are considered a more stable and suitable cell source for renal stem/progenitor cells.…”
Section: Renal Stem/progenitor Cells Differentiated From Pluripotent mentioning
confidence: 99%
“…For cell therapy aimed at repair of diseased kidneys (rather than creating whole new ones), there have been some reports on the beneficial effects of iPSC-derived nephron progenitor cell formulations in models of AKI. 12 A comparison of the latter with tissue-specific somatic precursors, such as expanded human nephron progenitors derived from fetal kidney, including analysis in CKD models, will be of importance. 13 In the case of in vivo manipulation, retention of iPSCs at the nephron progenitor state and lack of maturation have potential to carry increased risk for tumorigenicity, because these cells may serve as precursors for human Wilms tumors.…”
mentioning
confidence: 99%